2011
DOI: 10.1016/j.jcrs.2010.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of 219 human cadaver eyes with 1-piece or 3-piece hydrophobic acrylic intraocular lenses: Capsular bag opacification and sites of square-edged barrier breach

Abstract: There was no difference in central or peripheral PCO between 1-piece and 3-piece hydrophobic acrylic IOLs. With 1-piece IOLs, PCO tended to start at the optic-haptic junctions. With 3-piece IOLs, full anterior capsule coverage did not produce a statistically significant benefit with respect to PCO prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In a subset of this cadaver eye study, we analyzed capsular bag opacification and sites of peripheral PCO initiation in eyes with 1-piece and 3-piece hydrophobic acrylic IOLs. 27 For 3-piece hydrophobic acrylic IOLs, PCO initiation sites were recorded as at optic areas covered or In the analysis of plate silicone IOLs, our results confirm those in previous studies showing high rates of ACO and PCO with this IOL design. 5,16,17 All silicone plate IOLs were symmetrically fixated in the bag, and the degree of IOL decentration was, overall, mild in this group, even in the presence of asymmetric fibrosis and capsulorhexis phimosis.…”
Section: Discussionsupporting
confidence: 88%
“…In a subset of this cadaver eye study, we analyzed capsular bag opacification and sites of peripheral PCO initiation in eyes with 1-piece and 3-piece hydrophobic acrylic IOLs. 27 For 3-piece hydrophobic acrylic IOLs, PCO initiation sites were recorded as at optic areas covered or In the analysis of plate silicone IOLs, our results confirm those in previous studies showing high rates of ACO and PCO with this IOL design. 5,16,17 All silicone plate IOLs were symmetrically fixated in the bag, and the degree of IOL decentration was, overall, mild in this group, even in the presence of asymmetric fibrosis and capsulorhexis phimosis.…”
Section: Discussionsupporting
confidence: 88%
“…15 In general, clinical studies comparing PCO prevention between these IOLs and their 3-piece counterparts have not shown statistically significant differences. [16][17][18][19] Sacu et al 16 found that although eyes with 1-piece IOLs had slightly more PCO than eyes with 3-piece IOLs 1 year after implantation (PZ.002), the difference was no longer present after 2 years (PZ.3). In a study by Leydolt et al 17 1-piece and 3-piece hydrophobic acrylic IOLs had no significant difference in PCO intensity or neodymium: YAG laser treatment rate at the 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Leydolt et al 17 1-piece and 3-piece hydrophobic acrylic IOLs had no significant difference in PCO intensity or neodymium: YAG laser treatment rate at the 5-year follow-up. However, studies using rabbit models 4,11 and pseudophakic human eyes obtained postmortem 19 as well as clinical studies 12 found that when PCO occurred with the 1-piece Acrysof design, it had a tendency to start at the level of the optic-haptic junction. Because the haptics in this IOL are as thick as the optic component, there is a lack of barrier effect at the level of the optic-haptic junction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that acrylic IOLs appear to lose their PCO preventive effect, despite their sharp optic edges (27) . Although the Ioflex is a 1-piece lens, this not considered to be a factor in the development of PCO, since both 1-and 3-piece IOLs have been studied to evaluate their influence on PCO formation and no statistically significant differences between them have been found (28,29) . PCO is also age-dependent, being more frequently observed as a postoperative complication in young people and children (7,30) .…”
Section: Discussionmentioning
confidence: 99%